Eine (un-)wissenschaftliche Response - Frey, Jörg (Forum Exegese und Hochschuldidaktik: Verstehen von Anfang an, 2022)
The following response reflects on the status of exegesis within theological education from a personal stance. The respondent positions himself not only as an engaged teacher and researcher of New Testament exegesis, but also as an active part of a congregation in the Swiss Reformed Church. Looking back on his own journey through life in university and church, as well as on the ever-changing history of the connections between theory and praxis, he covers three main fields of attention: The altered circumstances of theological faculties and churches in the German speaking world, the dynamics of change in the field of Biblical Studies, and observations from his own teaching experience.